2004
DOI: 10.1097/01.phm.0000107486.99756.c7
|View full text |Cite
|
Sign up to set email alerts
|

Trunk Muscle Strength in Relation to Balance and Functional Disability in Unihemispheric Stroke Patients

Abstract: The findings indicate trunk flexion and extension muscle weakness in unihemispheric stroke patients, which can interfere with balance, stability, and functional disability.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
172
1
30

Year Published

2004
2004
2023
2023

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 259 publications
(210 citation statements)
references
References 26 publications
7
172
1
30
Order By: Relevance
“…In the Neutral condition the individuals with stroke had approximately 10% greater weight-bearing on their non-paretic limb while controls were nearly symmetrical. Although trunk control is often impaired following stroke (Dickstein et al 2004;Karatas et al 2004), we observed no noticeable differences in the way the individuals with stroke shifted their body to adjust limb load compared to our controls.…”
Section: Resultscontrasting
confidence: 71%
“…In the Neutral condition the individuals with stroke had approximately 10% greater weight-bearing on their non-paretic limb while controls were nearly symmetrical. Although trunk control is often impaired following stroke (Dickstein et al 2004;Karatas et al 2004), we observed no noticeable differences in the way the individuals with stroke shifted their body to adjust limb load compared to our controls.…”
Section: Resultscontrasting
confidence: 71%
“…Apesar da dinamometria isocinética já ocupar quantidade considerável de informação na literatura científica desde muitas décadas 3,9,13,19,46 , constatamos que, para as medidas obtidas em testes realizados para os movimentos do tronco, as informações são um pouco mais escassas 1,11,28,50 .…”
Section: Discussionunclassified
“…O controle do tronco portanto, apresenta-se como eixo central para a maioria das atividades físicas, na mobilidade e nas atividades do dia a dia como marcha, equilíbrios e transferências 28 .…”
Section: Doenças Cerebrovasculares Fraqueza Muscular E Reabilitaçãounclassified
See 2 more Smart Citations